SYSTEM APPROACH TO WEB APPLICATION SECURITY: ANALYSIS OF THREATS AND METHODS OF CYBER PROTECTION - Ilienko, Anna; Spys, Denys; Halata, Liliia; Dubchak, Olena (Ukrainian Information Security Research Journal, 2024)
The study focuses on analyzing common vulnerabilities in web applications, their impact on information system security, economic, reputational, and legal consequences, as well as methods for their detection and mitigation. A comprehensive review of the current state of web application security is conducted, including statistical data on current threats, analysis of attack trends, and an overview of the most notable incidents in recent years. Special attention is given to comparing different approaches to vulnerability classification, including OWASP Top 10, CWE Top 25, MITRE ATT&CK, NIST SP 800-53, and other standards, to evaluate their effectiveness and practical applicability. The study examines web application security testing methods, including static (SAST), dynamic (DAST), and interactive application security testing (IAST), as well as the potential of artificial intelligence (AI) and machine learning (ML) for automated threat detection. The advantages and limitations of different cybersecurity methods are analyzed, along with practical aspects of their implementation in real-world scenarios. Additionally, a detailed analysis of the impact of vulnerabilities on organizations is presented, covering economic consequences (direct financial losses, response costs, market value decline), reputational risks (loss of user trust, brand damage), and legal repercussions (fines, lawsuits, regulatory compliance requirements). The results of the study contribute to forming a comprehensive approach to risk minimization, including the implementation of advanced security analysis methods, adherence to international security standards, and the application of modern cybersecurity tools. This ensures more efficient detection and mitigation of threats at the early stages of web application development and operation.